Kajian Etika Digital Citizenship Berbasis Kearifan Lokal: Bedah Nilai Serat Sana Sunu - Azizah Miraj Nanda (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
The decline of digital civility in Indonesia, reflected in the widespread circulation of hoaxes, hate speech, and cyberbullying, indicates a growing crisis of communication ethics in digital spaces. This study aims to analyze the ethical values contained in Serat Sana Sunu by R.Ng. Yasadipura II and reconstruct their relevance to the concept of culturally grounded digital citizenship. This research employed a descriptive qualitative method using Hans-Georg Gadamer’s philosophical hermeneutic approach. The primary data consisted of Serat Sana Sunu, particularly Pupuh Dhandhanggula IX, which were analyzed through close reading, textual interpretation, and contextualization with contemporary digital ethical issues. The findings reveal five major clusters of ethical values: self-control, information integrity, critical literacy, communication etiquette, and social responsibility. Values such as tepa salira (empathy and tolerance), andhap asor (humility), and prudence in speech are highly relevant in mitigating hoaxes, cyberbullying, and aggressive communication behavior in digital media. The discussion demonstrates that a local wisdom-based ethical approach can complement the legal-formal perspective that has predominantly shaped digital citizenship discourse. This study concludes that Serat Sana Sunu provides a culturally rooted ethical framework for strengthening digital literacy education and fostering more reflective, humane, and responsible digital citizens